Procalcitonin Accurately Identifies Hospitalized Children With Low Risk of Bacterial Community-Acquired Pneumonia. (3rd February 2017) - Stockmann, Chris; Ampofo, Krow; Killpack, Jarrett; Williams, Derek J; Edwards, Kathryn M; Grijalva, Carlos G; Arnold, Sandra R; McCullers, Jonathan A; Anderson, Evan J; Wunderink, Richard G; Self, Wesley H; Bramley, Anna; et al.
Abstract: Background: Lower procalcitonin (PCT) concentrations are associated with reduced risk of bacterial community-acquired pneumonia (CAP) in adults, but data in children are limited. Methods: We analyzed serum PCT concentrations from children hospitalized with radiographically confirmed CAP enrolled in the Centers for Disease Control and Prevention's Etiology of Pneumonia in the Community (EPIC) Study. Blood and respiratory specimens were tested using multiple pathogen detection methods for typical bacteria (eg, Streptococcus pneumoniae, Haemophilus influenzae, Staphylococcus aureus ), atypical bacteria ( Mycoplasma pneumoniae and Chlamydophila pneumoniae ), and respiratory viruses. Multivariable regression was used to assess associations between PCT concentrations and etiology and severity. Results: Among 532 children (median age, 2.4 years; interquartile range [IQR], 1.0–6.3), patients with typical bacteria had higher PCT concentrations (±viruses; n = 54; median, 6.10; IQR, 0.84–22.79 ng/mL) than those with atypical bacteria (±viruses; n = 82; median, 0.10; IQR, 0.06–0.39 ng/mL), viral pathogens only ( n = 349; median, 0.33; IQR, 0.12–1.35 ng/mL), or no pathogen detected ( n = 47; median, 0.44; IQR, 0.10–1.83 ng/mL) ( P < .001 for all). No child with PCT <0.1 ng/mL had typical bacteria detected. Procalcitonin <0.25 ng/mL featured a 96% negative predictive value (95% confidence interval [CI], 93–99), 85% sensitivity (95% CI, 76–95), and 45% specificity (95% CI, 40–50) in identifying children without typical bacterial CAP. Conclusions: Lower PCT concentrations in children hospitalized with CAP were associated with a reduced risk of typical bacterial detection and may help identify children who would not benefit from antibiotic treatment.